An experimental biomechanical study of variants of monosegmental cervicospondylodesis and their effects on the adjacent vertebral motor segments - Barysh, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
An experimental biomechanical study of the quantitative and qualitative characteristics of the redistribution of the internal stress in CV-VI segment of a physical model of the cervical spine in different variants of monosegmental spondylodesis, as well as of the influence exerted by the stabilization of the above segment to adjacent segments CIV-V and CVI-VII, was made. It was revealed that a change of the internal stress in the region of the anterior and posterior support complex in both the stabilized segment and adjacent ones after modelling different variants of spondylodesis occurred in all the experimental situations and depended upon both the value of the moments of force and the fixation rigidness. The smallest disproportion of the internal stresses and, consequently, the smallest possibility for developing pathological changes at the adjacent levels in the postoperative period were observed in the situation of modelling the posterior spondylodesis with the smallest arm of force and a slight rigidness of fixation, as well as in the situation of modelling the rigid anterior interbody spondylodesis with an insignificant distraction of the ventral parts of the anterior support complex.